Owl sense - Darlington, Miriam (London : Guardian Faber Publishing, 2019)
"'Her softness took my breath away. Deadly beauty. She turned her face towards me. The owl's massive facial disc produces a funnel for sound that is the most effective in the animal kingdom'. Owls have captivated the human imagination for millennia. We have fixated on this night hunter as predator, messenger, emblem of wisdom, something pretty to print on a tote bag or portent of doom. Darlington sets out to tell a new story. Her fieldwork begins with wild encounters in the British Isles and takes her to the frosted borders of the Arctic. In her watching and deep listening to the natural world, she cleaves myth from reality and will change the way you think of this magnificent creature."--Publisher's description.
Includes bibliographical references (pages 337-342).
Keywords: Owls; Owls -- Behaviour